Perception of female users towards facilities management on high ropes activity at Skytrex Adventure Shah Alam - Abdul Hamid, Nurul Nazmira (2019)
Adventure based activities are exciting, challenging and both physically and mentally demanding. Some activities may be stressful and possibly hazardous. However, with proper understanding on the risk and safety measures, it will enhance quality experience. This study was conducted at Skytrex Adventure Shah Alam, Selangor. The purpose of this study were to identify users’ demographic profiles in enhancing quality experience on high ropes activity and to determine users’ perception towards facilities management safety on high ropes activity. The instrument used in the study was a structured questionnaire. This study considered several factors in doing high ropes activity such as safety, behaviour and characteristics, staffs and organization, equipment and infrastructure, activity and surrounding and weather. From the findings, the results showed that the percentage of females are higher than males in participating high ropes activity. Additionally, the study also found that females are more self-disciplined and they consider equipment inspection as an important safety aspect in order to gain quality experience. Besides, this study also found that young females made their own decision to participate in high ropes activity. The result also shows that females participated in high ropes activity to seek new experience and increase their self-confidence. To conclude, all the respondents gave positive perception about the safety of facilities management that will affect their quality experience.